Arable wildflowers have potential as living mulches for sustainable agriculture. (4th March 2021) - Rowntree, Jennifer K.; Dean, Clare; Morrison, Freddie; Brooker, Rob W.; Price, Elizabeth A. C.
ABSTRACT: Background: As agriculture has intensified, many once-common wildflowers have declined in arable landscapes, which has widespread implications for associated ecosystem services. The incorporation of sustainable practices, for example, growing living mulches (in-field, non-crop plant ground cover, maintained during the target crop growing season), can boost arable biodiversity, but few wildflower species have been utilised in this context. Aims: Our aim was to determine the suitability of arable wildflower species, once considered weeds, for use as living mulches. Methods: We first screened a number of arable wildflower species for germination when growing with a common cereal, barley ( Hordeum vulgare ). We then grew two ( Centaurea cyanus and Scandix pecten-veneris ) in pots in a glasshouse with and without barley, and grew barley alone to test the impact of the wildflowers on barley growth and biomass. Results: Neither of the wildflowers significantly negatively impacted barley biomass. Barley initially facilitated germination in S. pecten-veneris, but ultimately suppressed the above-ground biomass of both wildflowers. However, both wildflower species were able to coexist alongside barley. Conclusions: Our experiment provides evidence that wildflowers that were considered weeds in traditional agriculture have the potential to be grown alongside barley and could be incorporated as part of a living mulch.